Detector developments for a hybrid particle and radio array for cosmic-ray air-shower detection - Renschler, Max; Balagopal, Aswathi; Schieler, Harald; Schröder, Frank G.; Sulanke, Karl-Heinz; Weindl, Andreas; Weyrauch, Mark; Haungs, Andreas; Huber, Thomas; Huege, Tim; Karg, Timo; Kossatz, Marko; et al. (Journal of Physics: Conference Series, 2019)
Large-scale air-shower arrays could profit from a radio sub-detector as the radio emission in air showers is sensitive to the electromagnetic component. In particular, with an array of radio antennas in combination with particle detectors highly inclined EAS can be detected. This gives rise to new science cases, e.g. the search for PeV gamma rays coming from the Galactic Center at the South Pole, from where it is visible all over the year at an inclination of 61° degree. We report on progress and plans in the development of an optimized hybrid detector.